Defense decision-making method based on incomplete information stochastic game - Junnan YANG; Hongqi ZHANG; Chuanfu ZHANG (网络与信息安全学报)
Most of the stochastic game models to select network defense strategies are composed of matrix game and Markov decision,which assumes that the defender has known the attacker's revenue.This assumption does not conform to the actual situation.The uncertainty of the attacker's income was converted into the indeterminacy of the attacker type,and an incomplete information stochastic game model,which was combined with the static Bias game and Markov decision,was constructed.The equilibrium solution method of the incomplete information stochastic game model was given,and the strategy selection of the defender was guided by the stable Bias Nash equilibrium.Finally,a practical example was given to demonstrate the feasibility and effectiveness of the model.